2002
DOI: 10.1590/s0085-56262002000400007
|View full text |Cite
|
Sign up to set email alerts
|

Tempo de busca e de manuseio de larvas de Chrysoperla externa (Hagen, 1861) (Neuroptera, Chrysopidae) alimentadas com Uroleucon ambrosiae (Thomas, 1878) (Hemiptera, Aphididae)

Abstract: ABSTRACT. Searching and handling time of Chrysoperla externa (Hagen, 1861) (Neuroptera, Chrysopidae) larvae fed on Uroleucon ambrosiae (Thomas, 1878) (Hemiptera, Aphididae). The objective of this research was to determine the searching and handling times of three larval instars of C. externa fed on U. ambrosiae at densities of 30, 40 and 50 per vial, with the feeding of the larvae at the preceding instars being U. ambrosiae nymphs or Sitotroga cerealella (Olivier, 1819) eggs. The larvae were maintained at 25 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
2
2
0
1
Order By: Relevance
“…The handling time of C. externa larvae fed by U. ambrosiae, determined by Auad et al (2002), under similar conditions, was higher to that found in this study for all green lacewing instars, which may indicate that the C. cubana species can be considered an excellent biological controlling agent of H. foeniculi.…”
Section: Searching Time and Handlingsupporting
confidence: 61%
See 2 more Smart Citations
“…The handling time of C. externa larvae fed by U. ambrosiae, determined by Auad et al (2002), under similar conditions, was higher to that found in this study for all green lacewing instars, which may indicate that the C. cubana species can be considered an excellent biological controlling agent of H. foeniculi.…”
Section: Searching Time and Handlingsupporting
confidence: 61%
“…In the second instar of C. cubana, there was no statistical difference in searching time as a function of feeding in the preceding larva stage (Table 4), as observed by Auad et al (2002), who studied the searching time for Chrysoperla externa (Hagen) (Neuroptera: Chrysopidae) in Uroleucon ambrosiae (Thomas) (Hemiptera: Aphididae). The same result was found in the third instar of the predator, where no significant difference was observed in the searching time regarding the food used in previous instars.…”
Section: Searching Time and Handlingmentioning
confidence: 66%
See 1 more Smart Citation
“…The functional response identified (Type II) is similar with the response identified by Fonseca et al (2000), Auad et al (2001), Castro et al (2016) and Palomares-Pérez et al (2019), who mention that C. externa presented a Type II functional response when feeding on Schizaphis graminum (Rondani), Uroleuconambrosiae (Thomas) (Hemiptera: Aphididae), Trialeurodes vaporariorum Westwood (Hemiptera: Aleyrodidae) and Melanaphis sacchari (Zehntner) (Hemiptera: Aphididae) respectively. Similarly, C. rufilabris presents the same functional response when feeding on Aphis gossypii Glover (Homoptera: Aphididae) and Rhinocapsus vanduzeei Uhle (Hemiptera: Miridae).…”
Section: Resultssupporting
confidence: 83%
“…Entre los insectos, Chrysoperla externa Hagen 1861, "león de áfidos", es un depredador eficaz en el manejo ecológico e integrado de plagas, pudiendo habitar un gran número de agroecosistemas (Núñez, 1988;Aud et al, 2001;Iannacone et al, 2007). Las larvas son muy voraces y se alimentan preferentemente de insectos de cuerpo blando (Soto y Iannacone, 2008).…”
Section: Introductionunclassified